Cultural Crisis of Caste Renouncer: A Study of Dasnami Sanyasi Identity in Nepal - Giri, Madhu (Molung Educational Frontier, 2019)
Jat Nasodhanu Jogiko is a famous mocking proverb to denote the caste status of Sanyasi because the renouncer has given up traditional caste rituals set by socio-cultural institutions. In other cultural terms, being Sanyasi means having dissociation himself/herself with whatever caste career or caste-based social rank one might imagine. To explore the philosophical foundation of Sanyasi, they sacrificed caste rituals and fire (symbol of power, desire, and creation). By the virtues of sacrifice, Sanyasi set images of universalism, higher than caste order, and otherworldly being. Therefore, one should not ask the renouncer caste identity. Traditionally, Sanyasi lived in Akhada or Matha, and leadership, including ownership of the Matha transformed from Guru to Chela. On the contrary, Dasnami Mahanta started marital and private life, which is paradoxical to the philosophy of Sanyasi. Very few of them are living in Matha, but the ownership of the property of Mathatrans formed from father to son. The land and property of many Mathas transformed from religious Guthi to private property. In terms of cultural practices, Dasnami Sanyasi adopted high caste culture and rituals in their everyday life. Old Muluki Ain 1854 ranked them under Tagadhari, although they did not assert twice-born caste in Nepal. Central Bureau of Statistics, including other government institutions of Nepal, listed Dasnamiunder the line of Chhetri and Thakuri. The main objective of the paper is to explore the transformation of Dasnami institutional characteristics and status from caste renunciation identity to caste rejoinder and from images of monasticism, celibacy, universalism, otherworldly orientation to marital, individualistic lay life. Both philosophical orientation and behaviors are transformed. Who are the Dasnami Sanyasi? Why did the Dasnami Sanyasis campaign for the identity? How has the Dasnami Sanyasi been changing? Based on key informant interviews, observations in different Dasnami Sanyasi communities, their historical institutions, and self-reflection as a member of Dasnami Sanyasiare methods of data collection.